2007
DOI: 10.1681/asn.2006121348
|View full text |Cite
|
Sign up to set email alerts
|

Spiegelmer Inhibition of CCL2/MCP-1 Ameliorates Lupus Nephritis in MRL-(Fas)lpr Mice

Abstract: The monocyte chemoattractant protein CCL2 is crucial for monocyte and T cell recruitment from the vascular to the extravascular compartment at sites of inflammation. CCL2 is expressed in human lupus nephritis and was shown to mediate experimental lupus; therefore, CCL2 antagonists may be beneficial for therapy. This study describes the L-enantiomeric RNA oligonucleotide mNOX-E36, a so-called Spiegelmer that binds murine CCL2 with high affinity and neutralizes its action in vitro and in vivo. The mirror image c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
125
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 168 publications
(135 citation statements)
references
References 29 publications
8
125
1
1
Order By: Relevance
“…Covalent modifications of histone residues determine chromatin structure dynamics and transcription factor accessibility, i.e. epigenetic control of chromatin replication and gene transcription [5,13]. Not much is known about histone epigenetics in diabetes but a recent study suggested that high glucose levels activate the histone acetylases CBP and p/CAF to increase H3 acetylation which in turn leads to an elevated transcription of inflammatory genes in cultured monocytes [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Covalent modifications of histone residues determine chromatin structure dynamics and transcription factor accessibility, i.e. epigenetic control of chromatin replication and gene transcription [5,13]. Not much is known about histone epigenetics in diabetes but a recent study suggested that high glucose levels activate the histone acetylases CBP and p/CAF to increase H3 acetylation which in turn leads to an elevated transcription of inflammatory genes in cultured monocytes [16].…”
Section: Discussionmentioning
confidence: 99%
“…The accessibility of chromatin transcription factor binding sites is determined by the position and compaction of histones, proteins that wind up the double-stranded DNA in nucleosomes. Whether the nucleosomes are packed in the chromatin more or less tightly is determined by the activity of a number of enzymes that regulate the covalent modification of distinct amino acids in histones through processes such as acetylation, methylation and phosphorylation [3,13]. For example, histone H3 acetylation at lysines 9, 14, 18 and 23 or mono-or dimethylation at lysine activate chro-matin for transcription factor binding while histone H3 dior trimethylation at lysines 9 and 27 rather silence chromatin by inhibiting transcription factor accessibility [32].…”
Section: Introductionmentioning
confidence: 99%
“…24 The members of the chemokine family specifically direct different leukocyte subsets by distinct chemokine receptors into different renal compartments. 63 For example, the chemokine CCL2 recruits CCR2 + proinflammatory macrophages and T cells into the glomerulus and the tubulointerstitium, 64,65 whereas CCR1 + cells only recruit to the interstitial compartment and not to the glomerulus in LN. 66 Other leukocyte subsets involve other chemokines and chemokine receptors for their recruitment into the kidney.…”
Section: Intrarenal Pathogenic Mechanisms Of Lnmentioning
confidence: 99%
“…Spiegelmer antagonists to a number of extracellular targets have been described (11,14,24,35). Two Spiegelmers have proven to be safe and well tolerated in Phase I clinical studies 4 providing evidence that the Spiegelmer technology is suitable to generate human medicines.…”
Section: Discussionmentioning
confidence: 99%